Strategy for Development of Micro, Small and Medium Enterprises (MSMEs) in Palangka Raya City Facing the Industrial Revolution 4.0 - Adam Puja Mahendra; Benius Benius; Sabirin Sabirin (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2022)
This study aims to determine the characteristics of MSMEs in the city of Palangka Raya and analyze the strategy of developing MSMEs in the city of Palangka Raya based on the internal and external situation of MSMEs. The sample used in this study amounted to 45 MSMEs in the city of Palangka Raya. The types of data used are primary and secondary data. This study uses descriptive analysis tools, environmental analysis (internal and external), and SWOT analysis. The results of this study indicate that the characteristics of MSMEs in Palangka Raya City are more dominant in the trading business sector with a percentage reaching 71.25%. In determining the MSMEs development strategy in Palangka Raya City, it is seen based on environmental analysis and SWOT analysis, which shows the position is in quadrant I where market penetration and product development are strategies that can be used, then the SO (Strengths-Opportunities) strategy is a strategy that uses strength to take advantage of existing opportunities, expand distribution reach and establish cooperative/partnership relationships as alternative strategies in this analysis.